ANALISIS FRAMING PEMBERITAAN BOIKOT PERUSAHAAN MCDONALD DI INDONESIA PADA MEDIA KOMPAS.COM DAN KUMPARAN.COM - Heningtyas, Asshifa; Muhammad Thoyib Amali (LPPM Stikosa - AWS, 2024)
This study analyzes the framing of news about the McDonald's boycott in Indonesia published by two online media, Kompas.com and Kumparan.com. Using the framing analysis method, this study aims to understand how the two media outlets structure narratives related to the boycott triggered by McDonald's support for the conflicts that occur in Israel and Palestine. In this analysis, the author uses Robert Entman's framing model which includes four main elements: define problems, diagnose causes, make moral judgments, and suggest remedies. The results of the analysis show that Kompas.com tend to emphasize the economic and social aspects of the boycott, with an emphasis on market stability and consumer perspectives in Indonesia. On the other hand, Kumparan.com highlighted the political aspects and solidarity movements, by presenting the background of the conflict that triggered the boycott and opinions from various community groups. This difference in framing reflects the editorial approach of each media in shaping public opinion regarding the issue of the McDonald's boycott in Indonesia. This study contributes to an understanding of how media framing can affect public perception of controversial issues in economic, social, and political contexts.